857 The development of acute liver failure in paediatric intensive care. (17th August 2022) - Brady, Rebecca; Scarth, Jennifer; Mitchell, Jennifer
Abstract : Aims: Our primary aim was to assess patients who had acute liver complications on the paediatric intensive care unit (PICU) and identify any risk factors associated with this patient group to aid early identification of those at high risk of developing acute liver failure (ALF). Our secondary aim was to assess whether patients with ALF should be referred to gastroenterology earlier to allow for increased opportunity for further management, including referral for transplantation. Methods: A retrospective audit was undertaken looking at a sample size of 28 patients who developed ALF on PICU. The data was collected and analysed for indicators which may be associated with ALF including cardio-pulmonary bypass (CPB) time, RACHS-1 score, length of stay, abnormal liver function tests (LFTs), use of supportive therapies and treatment given. The data collected was then compared with current BSPGHAN guidelines for liver transplantation referral in ALF. 1 Results: 50% of patients had undergone cardiac surgery, within this group, each had a RACHS-1 score of > or = 2 and 86% required CPB. The average CPB time was 266 minutes. The average CPB time for the unit during this period was 183 minutes. Within the cohort, the duration of stay ranged from 1 – 78 days. Most patients had peak LFTs during days 1 – 3 of admission. 32% of patients had their ammonia levels measured, of those, 78% returned abnormal. 96% required invasive ventilation, 36% required renal support, 29% required ECMO and 86% required inotropic support. 75% of patients were given Vitamin K and 36% were given FFP. The mortality rate was 39%. The average mortality rate for the unit was 2.5 - 3%. Of the patients who died, 27% were referred to gastro, 45% required ECMO and 73% required renal support. In total, 18% of patients were referred to gastroenterology. Currently there are no guidelines used within PICU for referral to gastroenterology, therefore we assessed our cohort in line with the BSPGHAN guidelines. 1 93% met the criteria for referral to transplant centre. Conclusion: Most patients who developed ALF were less than one year of age and had a cardiac background. Through analysis of the cardiac cohort, we concluded that ALF was associated with a variety of cardiac operations, longer CPB time and a RACHS-1 score of > or = 2. Analysis of the entire cohort showed great variation between the length of stay, duration of invasive ventilation and the treatment given. Most patients had peak LFTs within days 1 – 3 of admission and the mortality rate in our cohort was much higher when compared to the unit average at that time. In addition, we concluded that a high proportion of patients who met the criteria for liver transplantation were not referred to gastroenterology. Presenting this audit to the PICU has led to increased awareness of ALF within PICU and highlighted the need to create guidelines for referral to gastroenterology for use in daily practice. Reference: Investigation and treatment of liver disease with acute onset, British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN).